2012
DOI: 10.5012/bkcs.2012.33.7.2200
|View full text |Cite
|
Sign up to set email alerts
|

One-Dimensional Core/Shell Structured TiO2/ZnO Heterojunction for Improved Photoelectrochemical Performance

Abstract: One-dimensional TiO 2 array grown on optically transparent electrode holds a promise as a photoelectrode for photoelectrochemical water splitting; however, its crystal structure is rutile, imposing constraints on the potent use of this nanostructure. To address this issue, a heterojunction with type-II band alignment was fabricated using atomic layer deposition (ALD) technique. One-dimensional core/shell structured TiO 2 /ZnO heterojunction was superior to TiO 2 in the photoelectrochemical water splitting beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Moreover, optical properties of TiO 2 nanomaterials are very interesting. It is well known that the anatase-TiO 2 presents a higher bandgap value (3.2 eV) than the rutile-TiO 2 (3.0 eV) [11]. The band gap value of anatase-TiO 2 is almost similar to that of ZnO nanomaterials (3.3 eV) [6].…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, optical properties of TiO 2 nanomaterials are very interesting. It is well known that the anatase-TiO 2 presents a higher bandgap value (3.2 eV) than the rutile-TiO 2 (3.0 eV) [11]. The band gap value of anatase-TiO 2 is almost similar to that of ZnO nanomaterials (3.3 eV) [6].…”
Section: Introductionmentioning
confidence: 96%
“…The perfect conformality of coatings made by ALD opens new possibilities for the design of innovative photocatalysts. Systems like core/shell heterostructures composed of a nanoparticles of SnO 2 or TiO 2 , covered homogeneously by a ZnO film as a shell can then be accessible 23,24 . These heterostructures are particularly interesting for water photocatalytic cleaning applications.…”
Section: Introductionmentioning
confidence: 99%
“…Photovoltaic properties of DSSC constructed with ITO/TiO2/ZnO/N719 photoanode and Pt/ITO CE were investigated under solar simulator with AM1.5G simulated solar radiation. The layers and band alignment (Ji et al, 2012) with the movement of electrons as a result of photon absorption is shown in Fig. 4a and constructed solar cell's real color image is seen in Fig.…”
Section: Resultsmentioning
confidence: 99%